Pengembangan Sistem Pencarian Karya Akhir Berdasarkan Abstrak Menggunakan Full-Text Searching Di Sistem Informasi Perpustakaan Jurusan Teknik Elektro Universitas Negeri Jakarta - Erna Selviyanti; Hamidillah Ajie; Widodo (Puslitbang Sekawan Institute Nusa Tenggara, 2019)
The research was conducted to develop a search system undergraduated thesis based on abstract using full-text searching in Library Information Systems Department of Electrical Engineering State University of Jakarta. The feature fulltext search system is developed to facilitate students in finding undergraduate thesis based on abstract. By using the select clause MATCH () ... Against, the data can be searched ordered by relevancy value. The research was conducted in the laboratory of multimedia Department of Electrical Engineering Faculty of Engineering, State University of Jakarta from September 2012 to December 2012. Development cycle of full-text search system conceptually consists of the design and analysis of systems, retrieval system development, integration of full-text search system to test SIPEL SIPEL 2013 and 2013. Full-text search system stores abstract 229 thesis abstract (undergraduate thesis, comprehensive, and TA) using XAMPP web server applications. Library Information Systems Department of Electrical Engineering State University of Jakarta (SIPEL 2013) has successfully integrated the SIPEL 2012 by adding databases and full-text search feature. The research use scripting language PHP and the MySQL database and worked on the Linux operating system by using a text editor Bluefish Editor and XAMPP as localhost server.